2018
DOI: 10.1177/2165143418779989
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Expectations of Peer Mentors Within Inclusive Higher Education Programs for Students With Intellectual Disability

Abstract: Although peer mentors play a prominent role in supporting higher education experiences for people with intellectual and developmental disabilities (IDD), little is known about these college students and the factors leading to their decision to become involved in this particular experience. We examined the motivations, experiences, and expectations of 250 peer mentors attending five diverse universities offering inclusive postsecondary programs for students with IDD. Nearly all (93.7%) of the entering peer ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Most studies reported either the age ( n = 15 studies) and/or academic year ( n = 18 studies) of these peers; nine studies reported neither. Only two studies (Carter et al, 2019; Farley et al, 2014) made reference to whether any peers themselves had disabilities. Most studies ( n = 21) provided some summary of the different areas of study peers were pursuing (e.g., majors, minors, colleges).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported either the age ( n = 15 studies) and/or academic year ( n = 18 studies) of these peers; nine studies reported neither. Only two studies (Carter et al, 2019; Farley et al, 2014) made reference to whether any peers themselves had disabilities. Most studies ( n = 21) provided some summary of the different areas of study peers were pursuing (e.g., majors, minors, colleges).…”
Section: Resultsmentioning
confidence: 99%
“…Peers without IDD have served as a common source of support for students enrolled through these IPSE programs (Carter et al, 2019; Grigal et al, 2019). The nature of their involvement, however, varies widely within and across campuses.…”
mentioning
confidence: 99%
“…Similar to other post-secondary education peer mentoring programmes, a goal of the SPS-PM programme is to provide the mentees with a samesex peer mentor to whom they may more closely relate (Carter et al, 2018;Griffin et al, 2016). First, despite the widespread efforts to recruit peer mentors across campus, the SPS-PM programme continues to struggle with issues of diversity related to gender, race/ethnicity and field of study.…”
Section: Impli C Ati On S For Future Pr Ac Ti Ce and Re S E Archmentioning
confidence: 99%
“…Education, Psychology, Pre-Medicine, Nursing and Social Work; Carter et al, 2018;Farley et al, 2014). For example, the SPS-PM core team strives to recruit undergraduates majoring in Human concerns about low productivity or poor quality of work performance due to lack of qualifications or necessary job skills (Kaye et al, 2011;Nota, Santilli, Ginevra, & Soresi, 2014); (c) concerns about how to provide accommodations and/or handle support needs of individuals with IDD (Kaye et al, 2011;Zappella, 2015);…”
Section: Impli C Ati On S For Future Pr Ac Ti Ce and Re S E Archmentioning
confidence: 99%
See 1 more Smart Citation